Job Satisfaction among Community School Teachers in Kathmandu District - Basnyat, Samjhana (ILAM इलम, 2023)
The purpose of the study was to find out the job satisfaction of teachers in Kathmandu district. This research was conducted among the population of teachers working in public secondary schools of Kathmandu district, focusing on job satisfaction. This study was based on a cross sectional survey method. To measure the teachers' job satisfaction, the researcher employed the questionnaire developed by him. The reliability and validity of the tool was ensured by the test retest method. The teachers who had been teaching Mathematics, English, Science, Computer and Social Subjects were not found satisfied. Except Nepali and mixed subject teachers, majority of all subject teachers were found neither satisfied nor dissatisfied whereas the majority of Science and Computer teachers' was seen in a satisfied category.